The mechanism of palmatine-mediated intestinal flora and host metabolism intervention in OA-OP comorbidity rats - Jie, Lishi; Ma, Zhenyuan; Gao, Yifan; Shi, Xiaoqing; Yu, Likai; Mao, Jun; Wang, Peimin (Frontiers in Medicine, 2023)
Background ErXian decoction is a Chinese herbal compound that can prevent and control the course of osteoarthritis (OA) and osteoporosis (OP). OP and OA are two age-related diseases that often coexist in elderly individuals, and both are associated with dysregulation of the gut microbiome. In preliminary work, palmatine (PAL) was obtained by liquid chromatography with tandem mass spectrometry (LC‒MS/MS) and network pharmacological screening. In this study, 16S rRNA sequencing and metabolomics were used to investigate the mechanism of PAL in the treatment of OA and OP. Methods The rats selected for this study were randomly divided into three groups: a sham group, an OP_OA group and a PAL group. The sham group was intragastrically administered normal saline solution, and the PLA group was treated with PAL for 56 days. Through microcomputed tomography (micro-CT), ELISA, 16S rRNA gene sequencing and nontargeted metabonomics research, we explored the potential mechanism of intestinal microbiota and serum metabolites in PAL treatment of OA_OP rats. Results PAL significantly increased the bone mineral density of femurs in OP_OA rats and improved cartilage damage. The intestinal flora analysis showed that PAL could also improve the intestinal flora disorder of OP_OA rats. For example, the abundance of Firmicutes, Bacteroidota, Actinobacteria, Lactobacillus, unclassified_f_Lachnospiraceae, norank_f_Muribaculaceae, Lactobacillaceae, Lachnospiraceae and Muribaculaceae increased after PAL intervention. In addition, metabolomic data analysis showed that PAL also improved the metabolic status of OP_OA rats. After PAL intervention, metabolites such as 5-methoxytryptophol, 2-methoxyacetaminophen sulfate, beta-tyrosine, indole-3-carboxylic acid-O-sulphate and cyclodopa glucoside increased. Association analysis of metabolomics and gut microbiota (GM) showed that the communication of multiple flora and different metabolites played an important role in OP and OA. Conclusion PAL affects the abundance of specific GM, regulates GM disorders, improves specific metabolites, and prevents and treats OP and OA. In addition, the application of GM and metabolomics association analysis provides a new strategy to reveal the mechanism of action of PAL in the treatment of OA and OP comorbidities.